2008
DOI: 10.1007/s10563-007-9036-y
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Ethene to Propene on Nickel Ion-loaded Mesoporous Silica Prepared by the Template Ion Exchange Method

Abstract: Although surface of amorphous silica is widely accepted to be neutral or slightly acidic, siliceous mesoporous materials have been found to act as excellent acid catalysts by us and other groups. On the other hand the increment in propene production is one of the significant objectives to be achieved in the present petroleum chemistry. Especially the one-path conversion of ethene to propene (ETP reaction, 3C 2 H 4 ? 2C 3 H 6 ) is the most desired process. In our efforts, the specific acid catalysis of mesoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 42 publications
2
45
0
4
Order By: Relevance
“…The Ni-doped catalyst prepared from FSM-16 showed greater activity than that prepared from MCM-41. Iwamoto et al [1,3] reported that Ni-MCM-41 has the unique ability to catalyze the direct formation of propylene from ethylene, which is selectively obtained via dehydration of ethanol on the MCM-41 prepared in their laboratory [4,16]. Therefore, the results shown in Figs Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ni-doped catalyst prepared from FSM-16 showed greater activity than that prepared from MCM-41. Iwamoto et al [1,3] reported that Ni-MCM-41 has the unique ability to catalyze the direct formation of propylene from ethylene, which is selectively obtained via dehydration of ethanol on the MCM-41 prepared in their laboratory [4,16]. Therefore, the results shown in Figs Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report suggests that propylene can be directly obtained from ethylene on MCM-41 (#41 of Mobile Composition of Matter) doped with nickel cations (Ni-MCM-41) [1]. It is generally known that propylene, ethylene, and other petroleum-related compounds are commonly produced by thermal cracking of naphtha.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In catalysis, mesoporous materials supported metal and metal oxide nanoparticles have received extensive attention [21][22][23][24]. Iwamoto and Kosugi [23] and Iwamoto [24] reported that the ethane-topropene reaction could be catalyzed on nickel ion-loaded mesoporous silica catalysts. The acidity of 1.4-MS and by limitations on the diffusion of reactants and the intermediate products.…”
Section: Characterizationmentioning
confidence: 99%
“…The nickel ions incorporated into the ordered mesoporous materials (OMMs) have also been suggested as efficient catalysts for the gas-phase transformation of ethylene to propylene [25][26][27][28][29][30][31][32][33][34]. For instance, the performance and durability of Ni/MCM-41 catalysts prepared from a nickel citrate precursor was ranked as auspicious with a promising potential for closing the gap between the propylene demand and supply [35].…”
Section: Introductionmentioning
confidence: 99%